(untitled) - Rosegger, Gerhard (Oxford, 1986)
The role of technology and innovation in increasing the competitiveness of firms and industries in domestic and international markets is of major concern to economists, industrial managers and public officials. The author provides an introduction into the economic analysis of production and technological change, exploring innovation, in the broadest sense, as an economic activity.
Keywords: Đổi mới công nghệ,Technological innovations; Khía cạnh kinh tế,Economic aspects